2006
DOI: 10.1002/chem.200500853
|View full text |Cite
|
Sign up to set email alerts
|

Fine Tuning of the Electronic Properties of Linear π‐Conjugated Oligomers by Covalent Bridging

Abstract: A series of oligothienylenevinylenes, pi-conjugated oligomers rigidified by ethylene bridges attached at different sites of the conjugated backbone, have been constructed by multistep synthetic methodologies. Electronic absorption spectra show that the rigidification of the conjugated system produces a bathochromic shift of the absorption maximum and a narrowing of the HOMO-LUMO energy gap, as compared to the spectra of an open-chain reference compound. The cyclic voltammograms of all oligomers show that these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 58 publications
0
24
0
Order By: Relevance
“…As expected, covalent rigidification of the precursor produces a significant reduction of the band gap of the corresponding polymer; however, the magnitude of this reduction is limited by the remaining possible inter‐ring rotations in the conjugated backbone. More recent work has shown that covalent rigidification is also effective for reducing the gap of extended oligo(thienylene vinylene)s 23. To summarize, covalent rigidification of π‐conjugated systems represents an efficient strategy for band gap control.…”
Section: Synthetic Principles For Band‐gap Engineering “The Tool Box”mentioning
confidence: 99%
“…As expected, covalent rigidification of the precursor produces a significant reduction of the band gap of the corresponding polymer; however, the magnitude of this reduction is limited by the remaining possible inter‐ring rotations in the conjugated backbone. More recent work has shown that covalent rigidification is also effective for reducing the gap of extended oligo(thienylene vinylene)s 23. To summarize, covalent rigidification of π‐conjugated systems represents an efficient strategy for band gap control.…”
Section: Synthetic Principles For Band‐gap Engineering “The Tool Box”mentioning
confidence: 99%
“…Several publications have shown that the hybrid functional B3LYP is adequate for studying the electronic structures of π-conjugated systems such as those involving a phosphole moiety, [34] EDOT [35] or π-conjugated oligomers. [36] Second derivatives were calculated in order to check that the optimised structures are true minima on the potential energy surface. All total energies have been zero-point-energy (ZPE) and temperature-corrected using unscaled density functional frequencies.…”
Section: Theoretical Sectionmentioning
confidence: 99%
“…It is known that the highest occupied molecular orbitallowest unoccupied molecular orbital (HOMO-LUMO) energy gap of π-conjugated systems containing heteroaromatic units depends on various structural factors such as bond length alternation, planarity, aromatic resonance energy, and electronic effects promoted by side chain substituents. 8 In the present study, the spectral and photophysical properties of three of these alternating copolymers were investigated in solution (room and low temperature) and in the solid state (thin films). With one of the copolymers, samples of two different molecular weights and polydispersities were studied to see whether this has any effects on either photophysical or film-forming properties.…”
Section: Introductionmentioning
confidence: 99%